Naked City. The Death and Life of Authentic Urban Places (excerpts) - Zukin, Sharon (Journal of Economic Sociology, 2018)
“Naked City” continues the Prof. Sharon Zukin’s earlier books (“Loft Living” и “Cultures of Cities”) and updates her views on how people use culture and capital in New York. Its focus is on a conflict between city dwellers’ desire for authentic origins and new beginnings, which many contemporary megalopolises met. City dwellers wish to defend own moral rights to redefine their places for living under upscale constructions, rapid growth and ethics of standartization. The author shows how in the frameworks of this conflict they construct the perceived authenticity of common and uncommon urban places. Each book chapter tells about various urban spaces, uncovering different dimensions of authenticity in order to catch and explain fundamental changes in New York emerged in the 1960s under mixed influences of private investors, government, media, and consumer tastes. The Journal of Economic Sociology publishes the “Introduction. The City That Lost Its Soul”, where the author explains the general idea of the book. Here she discusses reasons for emerging and history of social movement for authenticity, having combated with the government and private investors since the 1960s. Prof. Zukin also traces a transformation of the concept of authenticity: from property of person to property of thing to property of life experience and power.